Modeling the effect of exchange rate regimes on inflation dynamics: empirical evidence from Algeria - Gouasmia, Mohammed; Aoudia, Kahina (The journal of contemporary issues in business and government, 2023)
This study aims to economically measure the impact of exchange rate regimes, under the real classification of Reinhart and Rogoff (2017), on inflation dynamics in Algeria. The analysis period chosen was from 1985 to 2020, using the Fully Modified OLS in the long term and Error Correction Model in the short term. The study found a significant long-term negative relationship between the crawling peg exchange rate regime and inflation, while there was no relationship between exchange rate regimes and inflation in the short term.